DESIGNING EXERCISES ACCORDING TO THE AMERICAN COLLEGE TESTING (ACT) APPROACH TO ASSESS STUDENTS’ SCIENTIFIC THINKING COMPETENCE IN TEACHING THE TOPIC “ECOLOGY AND ENVIRONMENT” IN BIOLOGY GRADE 12 - Mau Hoang Quan, Nguyen; Thi Thanh Hoi, Phan; Thi Lan Anh, Bui (HNUE Journal of Science: Journal of Educational Science, 2025)
In the context of the ongoing shift from content-based to competence-based education, the development of assessment tools that validly and reliably measure student competencies has become an essential priority. This study addresses this need by proposing and operationalizing a framework for assessing scientific thinking competence, drawing on the structure of the American College Testing (ACT) approach. The framework encompasses three core components: (1) Interpretation of Data (IOD); (2) Scientific Investigation (SIN); and (3) Evaluation of Models, Inferences, and Experimental Results (EMI). The study’s principal contribution lies in translating this conceptual structure into a systematic process for designing ACT-oriented assessment instruments that extend beyond factual recall to capture higher-order cognitive processes. Applying this process to the Grade 12 Biology topic “Ecology and Environment” resulted in the development of 22 item clusters, comprising 160 questions in four formats: choice, short answer, true/false, and drag-and-drop, illustrating a practical pathway for embedding competence-based assessment into science education to more effectively evaluate and promote advanced levels of student thinking.